2022
DOI: 10.3390/brainsci12091263
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability of Dynamic Default Mode Network Connectivity Negatively Correlates with Suicidality in Major Depressive Disorder

Abstract: Previous studies have demonstrated that the suicidality in patients with major depressive disorder (MDD) is related to abnormal brain functional connectivity (FC) patterns. However, little is known about its relationship with dynamic functional connectivity (dFC) based on the assumption that brain FCs fluctuate over time. Temporal stabilities of dFCs within the whole brain and nine key networks were compared between 52 MDD patients and 21 age, sex-matched healthy controls (HCs) using resting-state functional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…(4) Temporal clustering coefficient [ 14 , 17 , 21 , 39 , 40 ]: This measure is also called “the temporal correlation coefficient”; it is derived from the definition of analogous metric (clustering coefficient) for conventional static networks. The temporal clustering coefficient estimates the tendency of a dynamic brain network to keep stable over time (its “temporal clustering”) by quantifying the average topological overlap of the network connections between any two consecutive layers (i.e., neighboring time windows).…”
Section: The Basic Concepts and Commonly Used Measures Of The Tempora...mentioning
confidence: 99%
See 2 more Smart Citations
“…(4) Temporal clustering coefficient [ 14 , 17 , 21 , 39 , 40 ]: This measure is also called “the temporal correlation coefficient”; it is derived from the definition of analogous metric (clustering coefficient) for conventional static networks. The temporal clustering coefficient estimates the tendency of a dynamic brain network to keep stable over time (its “temporal clustering”) by quantifying the average topological overlap of the network connections between any two consecutive layers (i.e., neighboring time windows).…”
Section: The Basic Concepts and Commonly Used Measures Of The Tempora...mentioning
confidence: 99%
“…Using the measure of temporal clustering coefficient, Zhao et al [ 39 ] found that patients with major depressive disorder showed decreased temporal stability at the global level and in regions of sensory perception systems. Hou et al [ 71 ] and Ouyang et al [ 40 ] found that patients with major depressive disorder showed decreased temporal stability within the striatum and default-mode regions, respectively. Overall, these findings suggest that major depressive disorder may be associated with excessive fluctuation (decreased temporal stability) of functional brain network organizations, and the default-mode areas are most prominently involved.…”
Section: Research Progress On Possible Relationships Between the Temp...mentioning
confidence: 99%
See 1 more Smart Citation
“…(4) The temporal clustering coefficient [14,17,21,39,40]: this measure is also called "the temporal correlation coefficient"; it is derived from the definition of analogous metric (clustering coefficient) for conventional static networks. The temporal clustering coefficient estimates the tendency of a dynamic brain network to keep stable over time (its "temporal clustering") by quantifying the average topological overlap of the network connections between any two consecutive layers (i.e., neighboring time windows).…”
Section: The Basic Concepts and Commonly Used Measures Of The Tempora...mentioning
confidence: 99%
“…Using the measure of temporal clustering coefficient, Zhao et al [39] found that patients with major depressive disorder showed decreased temporal stability at the global level and in regions of sensory perception systems. Hou et al [69] and Ouyang et al [40] found that patients with major depressive disorder showed decreased temporal stability within the striatum and default-mode regions, respectively. Overall, these findings suggest that major depressive disorder may be associated with excessive fluctuation (decreased temporal stability) of functional brain network organizations, and the default-mode areas are most prominently involved.…”
Section: Research Progress On Possible Relationships Between the Temp...mentioning
confidence: 99%